Strain engineered pyrochlore at high pressure - Rittman, Dylan R. (Sci Rep, 2017)
Strain engineering is a promising method for next-generation materials processing techniques. Here, we use mechanical milling and annealing followed by compression in diamond anvil cell to tailor the intrinsic and extrinsic strain in pyrochlore, Dy(2)Ti(2)O(7) and Dy(2)Zr(2)O(7). Raman spectroscopy, X-ray pair distribution function analysis, and X-ray diffraction were used to characterize atomic order over short-, medium-, and long-range spatial scales, respectively, under ambient conditions. Raman spectroscopy and X-ray diffraction were further employed to interrogate the material in situ at high pressure. High-pressure behavior is found to depend on the species and concentration of defects in the sample at ambient conditions. Overall, we show that defects can be engineered to lower the phase transformation onset pressure by ~50% in the ordered pyrochlore Dy(2)Ti(2)O(7), and lower the phase transformation completion pressure by ~20% in the disordered pyrochlore Dy(2)Zr(2)O(7). These improvements are achieved without significantly sacrificing mechanical integrity, as characterized by bulk modulus.